2019
DOI: 10.1177/0019793919875707
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Discrimination against Female Immigrants Wearing Headscarves

Abstract: Western countries have experienced a large influx of Muslim immigrants, and concomitantly the Muslim headscarf has become the subject of major controversy. Drawing on theories of stigma, social identity, and multiple discrimination/intersectionality, this study examines the effect of wearing this headscarf in the German labor market. The author applies the method of correspondence testing that allows measuring discrimination in a controlled field setting. Findings show that when applying for a job in Germany, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 48 publications
7
115
0
5
Order By: Relevance
“…However, dislike intersects with gender as previous researchers have argued (e.g., Diehl et al, ). Frequently, research demonstrates that women of Turkish origin are more likely to be discriminated against compared with women of German origin (e.g., Weichselbaumer, ). In the carpooling market, however, another scenario seems more probable.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…However, dislike intersects with gender as previous researchers have argued (e.g., Diehl et al, ). Frequently, research demonstrates that women of Turkish origin are more likely to be discriminated against compared with women of German origin (e.g., Weichselbaumer, ). In the carpooling market, however, another scenario seems more probable.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In daily life, Turkish minorities in Germany are often more likely to face discrimination in the labour market (e.g., Kaas & Manger, 2012;Koopmans, Veit, & Yemane, 2018;Pietrantuono, 2016;Schneider, Yemane, & Weinmann, 2014;Weichselbaumer, 2016), in the rental market (e.g., Auspurg, Hinz, & Schmid, 2017;Horr, Hunkler, & Kroneberg, 2018;Lütkenhöner, 2014;Sawert, 2019), in welfare offices (Hemker & Rink, 2017), in online auctions (Przepiorka, 2011), in schools (Sprietsma, 2013), and in the dating market (e.g., Lütkenhöner, 2014). A few studies found only limited support for the discrimination of Turkish minorities in the market for student housing (Diehl, Andorfer, Khoudja, & Krause, 2013) and in public administration when requesting information on childcare and mobile homes (Grohs, Adam, & Knill, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…iv Few studies distinguish between taste-based and statistical discrimination (Guryan and Charles, 2013). In her correspondence test study for Germany Weichselbaumer (2016) shows employer call-back rates to Muslim women wearing headscarves are lower than the employer call-back rates to otherwise identical women, a finding which appears to be consistent with taste-based discrimination.…”
Section: Resultsmentioning
confidence: 99%